Gestión del talento humano y servicio al cliente en los museos de la ciudad de Riobamba - Karina Michelle, Herrera Puente (2019)
The main objective of this research is to determine how human talent management influences the customer service of museums in Riobamba city, Chimborazo province. The research is documentary, field, descriptive and the design is correlational, not experimental. The study was conducted in two units of analysis, the first is the management of human talent and its dimensions: recruitment, selection, hiring and performance evaluation; A survey was applied to the administrators of the museums of Riobamba city with the use of a questionnaire using a Likert scale, the second unit of analysis is customer service with its dimensions: needs, expectations and customer satisfaction; A survey was applied to tourists with the use of an instrument using a Likert scale, with the data obtained, it leads to the verification of general and specific hypotheses through the application of the Chi-cuadrado test, concluding that talent management human and customer service with its dimensions does not influence the museums of Riobamba city, however in the situational diagnosis it determines that the recruitment and selection process of the staff is deficient, so at the end of the study a management by processes for the recruitment and selection of museum personnel oriented to endomarketing as an added value, which helps improve the human talent management through optimal personnel finding the appropriate requirements for the organization that supports the dissemination of museums, satisfying the needs of customers.